Diversity, potential and conservation of Annonaceae in Bogor Botanic Gardens, Indonesia - TRI HANDAYANI (Society for Indonesian Biodiversity, 2018)
Handayani T. 2018. Diversity, potential and conservation of Annonaceae in Bogor Botanic Gardens, Indonesia. Biodiversitas 19: 591-603. The Annonaceae is a large family of trees, shrubs and climbers consisting of about 109 genera and 2440 species. This family has important economic value for fresh fruit, cosmetics and perfumes, timber, traditional medicines, processed foods and beverages, insecticides, and ornamental plants. It also has an important role in forest ecosystems and in environmental management, as a key habitat organism. Despite its many uses, the family has not received special attention, and many of its species have been forgotten. Therefore, efforts are required to conserve the Annonaceae. Conservation of the Annonaceae depends upon ex-situ as well as in-situ methods. Conservation by ex situ approaches is considered effective because it can save from extinction species that are rare, endemic or of as yet recognized, unknown usefulness.The research reported in this paper aimed to determine Annonaceae diversity in Bogor Botanic Gardens (BBG), West Java, Indonesia as well as its current and potential utilization, with a view to developing ways of ensuring preservation of the collection within the Gardens. The study used direct observation of the Garden’s collection, compilation and scrutiny of relevant data from the long-term BBG registration database, analysis of past research data, and a literature study. Currently, BBG holds in its collection about 28 genera and 83 species of the Annonaceae family. The collection is estimated to cover 80% of the total species scattered across the Malesian region. Within the collection there are 49 tree species (59.04%), 14 shrub species (16.87%) and 20 liana species (24.09%). Most of the collections are from Java and Sumatra, while the fewest are from Maluku Islands and Papua. Among 40 species observed, 7 species are used for their fruit, 7 species have cosmetic or perfume uses, 22 species are a source of timber, 34 species have uses in traditional medicine, 6 species are used in the food or beverage industry, 19 species can be used as ornamental plants, 8 species for insecticides, and 4 species for other uses.The Annonaceae collections consist of young and old plants.Plants within the Gardens that are more than 100 years old include trees (7 species), shrubs (3 species) and a liana (1 species).The most widely used parts for traditional medicine are roots and leaves. This paper discusses the efforts taken by BBG to conserve the Annonaceae, include maintaining the diversity of the collection, researching the potential usefulness of the collection and exploring different approaches to its conservation.